The Environmental Emission and Climate Change Impact of Hydrogen Fuel Derived from Photocatalysis Water‐Splitting Reaction - Chloe Nelson; Meei Mei Gui; Peter K. J. Robertson (Advanced Energy & Sustainability Research)
Hydrogen fuel is widely received as the most promising clean fuel to substitute fossil fuel in power grid, home heating, and automotive industry to achieve net‐zero target. Photocatalysis hydrogen route, which fulfills the Gibbs free energy of water‐splitting reaction with solar energy, has been a promising approach to produce green hydrogen. However, there are limited study on the environmental performance of this hydrogen evolution process, particularly the potential emission of the photocatalyst synthesis process. In this work, the environmental emission of photocatalytic hydrogen evolution process is investigated through life cycle analysis (LCA) based on a pilot scale reaction system. The individual processing steps with its corresponding material flows that contributed significantly to environmental emission are identified from the LCA simulation. Excessive use of sacrificial reagent in the photocatalysis reaction has been identified as one of the main contributors to the environmental emission of this reaction system. The results observed can be feedback to the process design and improvisation of such photocatalysis reaction system to help improvise the existing technology for better environmental potential for upscale production to meet the ever‐rising demand on hydrogen fuel.